Efficacy and Safety of PrabotulinumtoxinA in Subjects With Benign Masseteric Hypertrophy: A Double-Blind, Randomized, Placebo-Controlled, Multicenter, Phase 3 Trial and Open-Label Extension Study - Seok, Joon; Koh, Young Gue; Hong, Jun Ki; Yun, So Hye; Kim, Da Hye; Son, Hyung Seok; Choi, Sun Young; Yoo, Kwang Ho; Lee, Yang Won; Kim, Beom Joon (Dermatologic surgery, 2024)
Despite the widespread use of botulinum toxin (BTX) injection for the treatment of masseter muscle hypertrophy (MMH), there is no standard treatment option. We report the efficacy and safety for BTX in MMH over a period of 48 weeks. In double-blinded, placebo-controlled phase 3 trials, 180 patients (randomized 1:1) received treatment with placebo (normal saline) or prabotulinumtoxinA (48 units). Masseter muscle thickness (at maximal clenching and resting positions), 3D imaging analysis, and masseter muscle hypertrophy scale grades were analyzed at each time point. After the 24-week CORE study, all patients who met the same criteria of the CORE study at week 24 ( n = 114) received only prabotulinumtoxinA, regardless of previous treatment, for an additional 24 weeks (48 weeks in total) for the open-label extension study. The largest differences in mean and percent changes from baseline in masseter muscle thickness were observed at 12 weeks, and there were significant differences between the 2 groups at all time points (all p < .001). The effect was independent of the number of injections. No serious adverse event was observed. PrabotulinumtoxinA could effectively ameliorate MMH without major complications.